Sistem Informasi Agenda Adat Banyuwangi Memanfaatkan Konversi Kalender Jawa ke Kalender Masehi - susanto, eko heri (Teknomatika, 2017)
Banyuwangi is one area which is located in East Java province. Banyuwangi has much natural tourism potentials, but to lead to the development of ecotourism, it is not enough to rely solely on natural tourism objects. So far, Banyuwangi district local government has promoted an agenda of indigenous cultures in Banyuwangi, but as long as this is done is still limited in BC is running, so that for subsequent years is not known exactly when the custom event will be held. This effect on the travelers who plan to visit Banyuwangi during the same event the following year, so that the tourists could not definitively scheduled arrival. A solution of these problems is to provide custom applications Banyuwangi agenda based website by using java calendar conversion to AD calendar, so for customary events in Banyuwangi upcoming schedule is already known for sure. In this study applies the algorithm to convert Kuwait Javanese calendar to calendar BC. Computation Urfi as in the Islamic calendar is based on the old average of one month synodic, namely 29.530589 days or 29 days 12 hours 44 minutes 2.9 seconds. The average is slightly larger than the 29.5 days. Figures 29.5 days is the middle value of 29 and 30. Thus the Islamic calendar arithmetically compiled by specifying the number of days in the month of Islam at 30 and 29 days alternately. The results of this study are able to produce custom website application Banyuwangi agenda, so as to determine the customary agenda in subsequent years are not confused anymore because it can be known at this time.Keywords— Indigenous Culture, Indigenous Agenda, Calendar Java